2019
DOI: 10.1155/2019/6856085
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Diagnostic Questionnaire for Damp Phlegm Pattern and Blood Stasis Pattern in Coronary Heart Disease Patients (CHD-DPBSPQ)

Abstract: Background. The aim was to develop a diagnostic questionnaire for damp phlegm pattern and blood stasis pattern in coronary heart disease patients (CHD-DPBSPQ). Methods. The standard procedures of questionnaire development were carried out to develop and assess CHD-DPBSPQ. The patients were assessed using the CHD-DPBSPQ, CHD-DPPQ, and CHD-BSPQ. Four methods were used to select the items on the CHD-DPBSPQ in a pilot study based on data from a Guizhou tertiary grade A hospital. Cronbach’s alpha and the split-half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Recently, many TCM diagnostic instruments have been developed to enable an systematic and reproducible measurement of TCM diagnostic patterns. 17 , 18 , 19 , 20 , 38 , 40 , 41 , 42 , 44 , 56 , 57 , 58 Unlike the disease specific instruments included in this review, some of those instruments measure specific TCM diagnostic construct directly without considering the disease entity per se . The Traditional Chinese Medical Diagnostic Descriptor was developed under this approach, with a goal of measuring TCM patterns regardless of the disease defined under Chinese or conventional medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many TCM diagnostic instruments have been developed to enable an systematic and reproducible measurement of TCM diagnostic patterns. 17 , 18 , 19 , 20 , 38 , 40 , 41 , 42 , 44 , 56 , 57 , 58 Unlike the disease specific instruments included in this review, some of those instruments measure specific TCM diagnostic construct directly without considering the disease entity per se . The Traditional Chinese Medical Diagnostic Descriptor was developed under this approach, with a goal of measuring TCM patterns regardless of the disease defined under Chinese or conventional medicine.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 , 16 Such TCM diagnostic instruments have been developed and validated for various conditions, including mental stress, 17 lateral elbow pain, 18 ulcerative colitis, 19 and coronary heart disease. 20 …”
Section: Introductionmentioning
confidence: 99%
“…When more than six experts assessed the questionnaire, the item-level content validity was not less than 0.78. 25,26 In addition, ten experts in the field were invited to test the questionnaire's content validity. The item-level content validity of the questionnaire ranged from 0.800-1.000, with only two items having a content validity of 0.900, one item having a content validity of 0.800, and the rest of the items having a content validity of 1.000.…”
Section: Introductionmentioning
confidence: 99%
“…The Coronary Heart Disease Damp Phlegm and Blood Stasis Pattern Questionnaire (CHD-DPBSPQ) is the standard metric for measuring CHD-DPBSP signs and symptoms in practice and clinical research [ 11 13 ]. The CHD-DPBSPQ was published in 2019 by combining an assessment of the damp phlegm pattern and blood stasis pattern in CHD Patients [ 14 ]. In other words, the CHD-DPBSPQ consists of two main domains that assess turbid phlegm and blood stasis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CHD-DPBSPQ has been shown to have a moderate diagnostic efficiency based on its receiver operating characteristic curves [ 12 ]. Some studies have shown that the CHD-DPBSPQ has high reliability and validity but the metric has yet to be assessed in a multicenter clinical trial [ 14 ]. The study's aim was to present research aimed at the test-retest reliability of the CHD-DPBSPQ in a multicenter clinical trial comprising CHD patients.…”
Section: Introductionmentioning
confidence: 99%